Multiobjective differential evolution algorithm-based sizing of a standalone photovoltaic water pumping system. (15th June 2016) - Muhsen, Dhiaa Halboot; Ghazali, Abu Bakar; Khatib, Tamer
Highlights: Multiobjective optimization algorithm is used to optimize the size of PVPS. The aggregated objective function composes of technical and economic objectives. A wide range sets of weights of objective functions are tested. Abstract: In this paper, a differential evolution based multiobjective optimization algorithm is proposed to optimally size a photovoltaic water pumping system (PVPS). Three weighted individual objectives are aggregated by a single function to optimize the configuration of PVPS. Loss of load probability, life cycle cost and the volume of excess water are considered as three individual objective functions. The proposed pumping system is supposed to provide a daily water volume of 30 m 3 with a static head of 20 m. The complexity of the initializing of the weights for each individual objective function is overcome by testing a wide range sets of weights. The performance of the system is tested based on hourly meteorological data. The performance results of the proposed system show that the loss of load probability and the average hourly water flow rate over a year time are around 0.5% and 3.297 m 3 /h, respectively. The life cycle cost, water deficit, and cost of water unit of the system are 9911 USD, 55.015 m 3, and 0.045 USD/m 3, respectively.